Nothochrysinae (Neuroptera: Chrysopidae) from the early Eocene Fur Formation, Denmark, with description of a new genus - Makarkin, Vladimir N.; Perkovsky, Evgeny E. (Zootaxa, 2024)
Furochrysa alisae gen et sp. nov. is described, and Stephenbrooksia multifurcata Willmann, 1993 and Danochrysa madseni Willmann, 1993 are re-described based on their holotypes and additional specimens from the early Eocene Fur Formation of Denmark. The very long crossvein 1icu between CuA and CuP in the hind wing distinguishes Furochrysa gen. nov. from all other Nothochrysinae. The hind wing venation of the holotype of S. multifurcata is strongly aberrant; in particular, its MA is deeply forked proximad the origin of RP, while it is not forked proximad the pseudocubitus in other Chrysopidae. The forewing venation of the three examined specimens of D. madseni show variability in the branching of the anterior branch of CuP and A2. The chrysopid assemblage of the early Eocene Fur Formation strongly differs from that of the late Paleogene (late Eocene/Oligocene) of Europe, while the nothochrysines of the early and late Paleogene of North America do not especially differ.